2021
DOI: 10.2196/20862
|View full text |Cite
|
Sign up to set email alerts
|

Towards The Automated, Empirical Filtering of Drug-Drug Interaction Alerts in Clinical Decision Support Systems: Historical Cohort Study of Vitamin K Antagonists

Abstract: Background Drug-drug interactions (DDIs) involving vitamin K antagonists (VKAs) constitute an important cause of in-hospital morbidity and mortality. However, the list of potential DDIs is long; the implementation of all these interactions in a clinical decision support system (CDSS) results in over-alerting and alert fatigue, limiting the benefits provided by the CDSS. Objective To estimate the probability of occurrence of international normalized rati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This approach has limited opportunities for improving specificity without compromising sensitivity. [17][18][19][20][21][22][23][24] Recent studies concluded that CDS systems should have greater flexibility to customize DDI alerting especially by adding contextual modulation, also called specificity modulation. [25][26][27] The term contextual modulation comes from neurobiology, being the change in the neurons' responsiveness to a stimulus caused by context.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…This approach has limited opportunities for improving specificity without compromising sensitivity. [17][18][19][20][21][22][23][24] Recent studies concluded that CDS systems should have greater flexibility to customize DDI alerting especially by adding contextual modulation, also called specificity modulation. [25][26][27] The term contextual modulation comes from neurobiology, being the change in the neurons' responsiveness to a stimulus caused by context.…”
Section: Articlementioning
confidence: 99%
“…Too many irrelevant alerts can lead to alert fatigue, 9,13–15 described as a “mental state being the result of too many irrelevant alerts consuming time and mental energy, which can cause important alerts to be ignored along with clinically unimportant ones.” 16 Basic DDI‐CDS systems have limited options for suppressing irrelevant DDI alerts, other than turning DDI alerts off for specific drug combinations. This approach has limited opportunities for improving specificity without compromising sensitivity 17–24 . Recent studies concluded that CDS systems should have greater flexibility to customize DDI alerting especially by adding contextual modulation, also called specificity modulation 25–27 .…”
mentioning
confidence: 99%
“…In order to prevent mistakes, alerts, defined as notifications or warnings that highlight the risk of danger, have been widely utilized in many fields [2][3][4]. This includes healthcare, where clinical decision support systems (CDSS) commonly use alerts to notify clinicians of actual or potential errors [5,6]. Previous studies have confirmed that alerts are an efficient way to prevent medication errors and streamline clinical workflow [7][8][9].…”
Section: Introductionmentioning
confidence: 99%